Intervertebral disc repair material based on staged treatment strategy for intervertebral disc degeneration and its preparation method and application

By developing a disc repair material based on the stage treatment strategy of intervertebral disc degeneration, the sandwich structure double electroactive stent and composite hydrogel is used to solve the problem of post-disc repair, achieving effective repair of intervertebral discs and improving biomechanical performance.

CN119405880BActive Publication Date: 2025-03-18WEST CHINA HOSPITAL SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510019876.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-18
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the symptoms of back pain and nerve compression caused by disc degeneration, especially when repair is required after discectomy.

Method used

Developed a disc repair material based on a staged treatment strategy for disc degeneration, including a sandwich structure dual electroactive stent and composite hydrogel, to promote the repair of disc defects by reconstructing an electroosmosis network and utilizing mechanical energy as electrical stimulation.

Benefits of technology

This material can treat the pathological characteristics of different stages of intervertebral disc degeneration, block the vicious cycle of inflammation and oxidative stress, promote nucleus pulposus repair, enhance cell migration ability, improve the biomechanical properties of defective intervertebral discs, reduce the intracellular ROS level under oxidative stress, delay cell aging and increase extracellular matrix content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405880B_ABST
    Figure CN119405880B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of biomedical materials, and discloses a disc repair material based on a staged treatment strategy for disc degeneration, and its preparation method and application; the disc repair material includes a sandwich structure dual electroactive stent, and a composite hydrogel attached to the dual electroactive stent; the sandwich structure dual electroactive stent includes a conductive porous stent with a conductive through-channel structure and a piezoelectric fiber film located on the upper and lower sides of the conductive porous stent; the composite hydrogel includes a hydrogel and an antioxidant nanozyme uniformly dispersed in the hydrogel; the antioxidant nanozyme is a core-shell structure nanoparticle with Co-Ni bimetallic oxide as the core and polydopamine as the shell. The present invention repairs the early degenerative disc through antioxidant and anti-inflammatory nanozymes, repairs the defective disc after resection with a dual electroactive stent, and the composite hydrogel enhanced by the electroactive stent can replace the late degenerative disc, thereby achieving corresponding treatment for different stages of disc degeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and relates to an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration, and a preparation method and application thereof. Background Art

[0002] Lower back pain has become a challenging health problem worldwide, affecting hundreds of millions of people, causing a large number of patients to become disabled and incapacitated every year, of which more than 40% are caused by degenerative disc disease. As a cartilage composite tissue with low cell density and no vascular structure, the degeneration process of the intervertebral disc is often accompanied by damage to the tissue structure and function, especially the degeneration of the nucleus pulposus, which will lead to a decrease in the overall biomechanical properties of the intervertebral disc, further causing severe back pain and nerve compression symptoms. The early pathological symptoms of intervertebral disc degeneration are the loss of extracellular matrix components in the nucleus pulposus and the decrease in the number of cells. At this time, there is a vicious cycle between redox imbalance and increased inflammatory levels in the local microenvironment, leading to aggravated degeneration; when the intervertebral disc degenerates to the middle stage, the annulus fibrosus structure is destroyed, protrusion occurs and compresses the nerves. At this time, discectomy is the most direct and effective means to relieve nerve compression, but if the intervertebral disc defect caused by surgery is not treated, it will cause re-protrusion of the nucleus pulposus and pathological slippage, etc., bringing the risk of secondary surgery; when the intervertebral disc degeneration develops to the late stage, its mechanical properties are severely damaged, and the intervertebral space is narrowed, at this time, the intervertebral disc needs to be replaced and repaired in an integrated manner.

[0003] There are two main clinical treatments for disc degeneration: conservative treatment and surgical treatment. After diagnosis and evaluation, if the disc degeneration is mild, conservative treatment is the first choice to relieve acute pain by relaxing muscles and improving nerve root edema caused by inflammation. Conservative treatment cannot stop the progression of disc degeneration. When the treatment effect is not significant or the disc degeneration worsens, surgical treatment is often required, but clinical surgical treatment often causes irreversible damage to the spine.

[0004] The annulus fibrosus is an anisotropic lamellar structure and has dual electrical activity of conduction and voltage. Currently, a large number of studies have reported the application of high-tensile strength biomaterials in the repair of annulus fibrosus. Based on the positive role of electroactive materials in the repair of other soft tissues (skin, articular cartilage, etc.), if biomaterials with electroactive functions can be developed and implanted into the intervertebral disc defect site, the interaction between electroactive materials and cells can be explored through in vitro biological experiments, and an animal intervertebral disc defect model can be constructed to clarify the biological process of electroactive materials promoting intervertebral disc regeneration and repair, it will not only provide a new strategy for post-discectomy treatment, but also broaden the application scenarios of electroactive materials in the field of tissue repair.

[0005] In addition, the rigid porous scaffold is hard but lacks toughness, which easily causes stress concentration at the rubber wire; the hydrogel is flexible but lacks certain rigidity, making it difficult to maintain the height of the intervertebral disc. The development of repair materials that match the natural mechanical properties of the intervertebral disc is also one of the technical problems to be solved by the present invention. Summary of the invention

[0006] The purpose of the present invention is to target treatment strategies at different stages of intervertebral disc degeneration and study their effects. The present invention provides an intervertebral disc repair material and a preparation method thereof based on a staged treatment strategy for intervertebral disc degeneration, targeting the unbalanced redox balance and inflammatory microenvironment in the nucleus pulposus in the early stage of intervertebral disc degeneration. The material promotes the repair of intervertebral disc defects after resection by rebuilding the electroosmotic network at the defect and converting the mechanical energy generated by daily activities into electrical stimulation.

[0007] Another object of the present invention is to provide application of the above material in preparing an intervertebral disc repair device.

[0008] The present invention mainly proposes corresponding treatment strategies based on the pathological characteristics of different stages of intervertebral disc degeneration:

[0009] ① Inject antioxidant nanozymes into early degenerative discs to block the vicious cycle between inflammation and oxidative stress and promote nucleus pulposus repair;

[0010] ② Aiming at the defect formed after discectomy, a piezoelectric conductive dual electroactive stent was constructed, and its effect on cell activity and disc repair was explored to expand the application scenarios of electroactive materials in the field of tissue repair;

[0011] ③ The hydrogel and porous scaffold were functionally modified respectively to give the hydrogel antioxidant function and the porous scaffold electroactive properties. A composite material system was constructed by reinforcing the functionalized hydrogel with the modified porous scaffold for the replacement repair of the intervertebral disc, and its effect on cell activity under different environments was preliminarily explored.

[0012] In order to achieve the first invention objective, the present invention can be implemented through the following technical solutions.

[0013] The present invention provides an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration, comprising: a sandwich-structured dual-electroactive stent, and a composite hydrogel attached to the dual-electroactive stent; the sandwich-structured dual-electroactive stent comprises a conductive porous stent with a conductive through-channel structure and piezoelectric fiber films located on the upper and lower sides of the conductive porous stent; the conductive porous stent is obtained by 3D printing with a 3D printing ink containing graphene; the composite hydrogel comprises a hydrogel and an antioxidant nanozyme uniformly dispersed in the hydrogel; the antioxidant nanozyme is a core-shell structured nanoparticle with a Co-Ni bimetallic oxide as a core and polydopamine as a shell.

[0014] The above-mentioned intervertebral disc repair material based on the staged treatment strategy of intervertebral disc degeneration, the 3D printing ink also includes a fat-soluble biodegradable material; the fat-soluble biodegradable material is at least one of polycaprolactone, polyhydroxyalkanoate, polylactic acid, etc.; the mass ratio of the fat-soluble biodegradable material to graphene is 9~10:1.

[0015] In the above-mentioned intervertebral disc repair material based on the staged treatment strategy for intervertebral disc degeneration, the piezoelectric fiber film is a polyvinylidene fluoride fiber film doped with barium titanate; the piezoelectric fiber film is obtained by electrospinning; and the mass ratio of polyvinylidene fluoride to barium titanate is 18~20:1.

[0016] In the above-mentioned intervertebral disc repair material based on the staged treatment strategy for intervertebral disc degeneration, the hydrogel is obtained by solidifying a hydrogel precursor solution containing polyvinyl alcohol and gelatin.

[0017] The present invention also provides a method for preparing the intervertebral disc repair material based on the above-mentioned staged treatment strategy for intervertebral disc degeneration, comprising the following steps:

[0018] (1) Preparation of a sandwich structure dual electroactive scaffold, including the following steps:

[0019] (11) preparing a 3D printing ink comprising a fat-soluble biodegradable material and graphene, and obtaining a conductive porous scaffold by 3D printing;

[0020] (12) preparing a polyvinylidene fluoride electrospinning solution in which barium titanate is uniformly dispersed, and forming a piezoelectric fiber film on the upper and lower sides of the conductive porous support by electrospinning;

[0021] (2) Preparing antioxidant nanozymes, comprising the following steps:

[0022] (21) Preparation of Co-doped NiO nanoparticles;

[0023] (22) Co-doped NiO nanoparticles are uniformly dispersed in deionized water, the resulting dispersion is mixed with a dopamine solution, and the pH is adjusted to 8-9, and stirred in the dark; the resulting product is centrifuged, washed, and freeze-dried to obtain an antioxidant nanozyme;

[0024] (3) Preparing a composite hydrogel precursor solution, comprising the following steps:

[0025] (31) adding polyvinyl alcohol to the glycerol aqueous solution, heating and stirring to dissolve, and obtaining a PVA hydrogel precursor solution;

[0026] (32) adding the antioxidant nanozyme to the PVA hydrogel precursor solution and dispersing it evenly, then adding gelatin and stirring until the gelatin is dissolved to obtain a composite hydrogel precursor solution;

[0027] (4) Preparation of intervertebral disc repair materials

[0028] The sandwich structure dual electroactive scaffold prepared in step (1) is immersed in the defoamed composite hydrogel precursor solution, subjected to repeated vacuum pumping-degassing operations for more than three times, and then subjected to repeated freezing-thawing operations for more than three times, and finally subjected to annealing treatment to obtain the electroactive scaffold-enhanced composite hydrogel, i.e., the intervertebral disc repair material.

[0029] In the above step (1), a conductive porous scaffold is first prepared by 3D printing technology, and then a piezoelectric fiber film is formed on the upper and lower sides of the conductive porous scaffold by electrospinning technology.

[0030] Specifically, in step (11), the mass ratio of the fat-soluble biodegradable material to the graphene is 9-10:1. The fat-soluble biodegradable material is at least one of polycaprolactone, polyhydroxyalkanoate, polylactic acid, etc. The fat-soluble biodegradable material is first dissolved in a first organic solvent, and then the graphene is evenly dispersed in the resulting solution to obtain a 3D printing ink; the resulting 3D printing ink is further stirred and mixed evenly. The first organic solvent is one of dichloromethane, tetrahydrofuran, etc. The amount of the first organic solvent used is measured by using 7-8 ml of the first organic solvent per 1 g of the fat-soluble biodegradable material.

[0031] In the present invention, the 3D printing parameters for the conductive porous scaffold are set as follows: extrusion pressure 0.5-0.6 MPa, printing speed 3-5 mm / min, layer thickness 0.16-0.20 mm, and printing wire gap 0.6-1 mm.

[0032] In step (12), first, barium titanate is uniformly dispersed in a second organic solvent, then polyvinylidene fluoride is added, and then stirred at 60-70°C for 6-8h to form a uniform white solution; cooled to room temperature, then a third organic solvent is added, and stirred to form an electrospinning solution; then, a piezoelectric fiber film is formed on the upper and lower sides of the conductive porous support by an electrospinning method, and then the residual solvent is removed by vacuum drying to obtain a sandwich structure dual electroactive support; the mass ratio of the polyvinylidene fluoride to barium titanate is 18-20:1. The second organic solvent is one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), etc. The amount of the second organic solvent used is measured by using 3 ml of the second organic solvent for every 0.025 g of barium titanate. The third organic solvent is one of acetone, ethyl acetate, butanone, cyclohexanone, etc. The amount of the third organic solvent used is measured by using 3-5 ml of the third organic solvent for every 1 g of polyvinylidene fluoride. In the present invention, the electrospinning parameters are set as: flow rate 0.05-0.1 mm / min, voltage 15-16 KV.

[0033] In the above step (2), Co-doped NiO nanoparticles are first prepared, and then polydopamine is generated on the surface of the Co-doped NiO nanoparticles as a shell to form a core-shell structured antioxidant nanozyme.

[0034] Specifically, in step (21), cobalt salt and 2-methylimidazole are dissolved in a fourth organic solvent at a molar ratio of 1:7-9 to obtain corresponding solutions, and then the two solutions are mixed and stirred for 10-15 minutes to obtain a uniform mixed solution; the mixed solution is allowed to stand, the precipitate is collected, and then washed and dried to obtain ZIF-67 powder; then the ZIF-67 powder and the nickel salt are mixed in a fifth organic solvent at a mass ratio of 1:1, stirred evenly, heated to 90-95°C for 1-2 hours, and then centrifuged, washed, and dried to obtain Co-Ni layered double hydroxide; the Co-Ni layered double hydroxide is calcined at 290-310°C for 3-3.5 hours to obtain Co-doped NiO nanoparticles. The cobalt salt is one of cobalt nitrate, cobalt chloride, etc.; the nickel salt is one of nickel chloride, nickel sulfate, etc. The fourth organic solvent is one of methanol, dimethyl sulfoxide, etc. The amount of the fourth organic solvent used is measured according to the molar volume ratio of cobalt salt to solvent of 5mmol:80-100mL. The fifth organic solvent is one of ethanol, isopropanol, dimethoxymethane, etc. The usage of the fifth organic solvent is measured according to the mass volume ratio of solute to solvent of 6 mg:1 mL.

[0035] In step (22), the concentration of Co-doped NiO nanoparticles in the dispersion is 0.6-0.75 mg / mL. The dopamine solution is obtained by adding dopamine to water and mixing evenly, and the concentration of dopamine is 2-3 mg / mL. The pH of the mixture of the dispersion and the dopamine solution is adjusted to 8-9 using Tris-hydrochloric acid buffer, and then stirred for 23-25 ​​hours in the dark.

[0036] In the above step (3), a composite hydrogel precursor solution is prepared based on polyvinyl alcohol, antioxidant nanozyme and gelatin; the final concentration of polyvinyl alcohol in the composite hydrogel precursor solution is 12%~18%w / v, the final concentration of antioxidant nanozyme is 0.5‰~1‰w / v, and the final concentration of gelatin is 4%~6%w / v.

[0037] Specifically, in step (31), the glycerol aqueous solution is obtained by mixing glycerol and water in a volume ratio of 2:8. Polyvinyl alcohol is added to the glycerol aqueous solution and stirred at 90-95° C. for 4-6 hours to dissolve.

[0038] In step (32), the PVA hydrogel precursor solution obtained in step (31) is cooled to 50-60°C, and then antioxidant nanoenzymes are added to disperse it evenly. After gelatin is added, it is stirred at the above temperature until the gelatin is completely dissolved, and the stirring time is 3-4 hours.

[0039] In the above step (4), the composite hydrogel is allowed to fully permeate the entire scaffold.

[0040] The vacuum pumping-degassing operation is: at 35-45°C, first evacuate until the vacuum degree drops below 100 Pa, maintain for 30-35 seconds, and then release to standard atmospheric pressure. The freezing-thawing operation is: freeze-thawing cycle between -20°C and room temperature; specifically, first cool to -20°C, then heat to room temperature. The annealing condition is annealing at 40-50°C for 4-6 hours.

[0041] The present invention also provides application of the above material in preparing an intervertebral disc repair device.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The intervertebral disc repair material provided by the present invention is based on the staged treatment strategy of intervertebral disc degeneration. The anti-oxidant and anti-inflammatory nanozymes are used to repair the early stage of degeneration of the intervertebral disc. The dual electroactive stents are used to repair the defective intervertebral disc after resection. The electroactive stent-enhanced composite hydrogel can replace the late stage of degeneration of the intervertebral disc, thereby achieving corresponding treatment according to the pathological characteristics of different stages of intervertebral disc degeneration.

[0044] (2) The antioxidant nanozymes provided by the present invention can block the vicious cycle between oxidative stress and inflammatory response, improve the state of nucleus pulposus cells, and transform them into an anabolic phenotype, which is expected to prevent or even reverse the process of intervertebral disc degeneration and promote the regeneration of damaged nucleus pulposus;

[0045] (3) The composite hydrogel provided by the present invention can reduce the level of ROS in cells under oxidative stress, reduce cell inflammatory response, delay cell aging and increase the content of extracellular matrix, and has the potential to improve the strong oxidation and high inflammation microenvironment of the defective intervertebral disc, restore cell metabolism and promote the repair of intervertebral disc defects; and gelatin increases the water content, swelling performance and degradation performance of the hydrogel matrix, which is beneficial to the diffusion of small molecule nutrients and metabolic wastes during tissue repair;

[0046] (4) The sandwich-structured dual-electroactive scaffold provided by the present invention can enhance the electrical output performance of the sandwich-structured scaffold by improving the conductivity of the middle sandwich scaffold or improving the piezoelectric properties of the fiber films on the upper and lower sides, and the two methods also have a synergistic improvement effect; moreover, the sandwich-structured dual-electroactive scaffold can generate point stimulation under ultrasonic excitation, which can improve the migration ability of stem cells and promote their recruitment through the barrier around the scaffold, which is of great significance for guiding endogenous stem cells to migrate to the defect;

[0047] (5) The electroactive scaffold-enhanced composite hydrogel provided by the present invention has mechanical properties that better match those of a natural intervertebral disc; and chondrocytes can adhere and spread on the surface of the composite hydrogel, which has the potential to promote the integration of the material with the surrounding intervertebral disc tissue. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The SEM test results of the sandwich structure dual electroactive scaffold prepared in Example 1 of the present invention; wherein (a) corresponds to the surface of the conductive porous scaffold G10, (b) corresponds to the cross section of the conductive porous scaffold G10, and (c) corresponds to the cross section of the sandwich structure dual electroactive scaffold G10B5;

[0049] Figure 2 This is the EDS test result of the sandwich structure dual electroactive stent prepared in Example 1 of the present invention;

[0050] Figure 3 The test results of the current output characteristics of the sandwich structure dual electroactive stent prepared in Example 1 of the present invention under cyclic stress;

[0051] Figure 4 The test results of the sandwich structure dual electroactive scaffold prepared in Example 1 of the present invention on the cell migration ability; wherein A corresponds to the schematic diagram of the Transwell migration experiment process, B corresponds to the crystal violet staining picture of the lower surface of the Transwell chamber, and C corresponds to the relative number of cells migrated to the lower surface of the Transwell; US+ indicates application of ultrasonic stimulation, and US- indicates no application of ultrasonic stimulation; G0 represents the porous scaffold obtained in step (11) without adding graphene, which serves as the control group;

[0052] Figure 5 TEM test results of the antioxidant nanozyme prepared in Example 2;

[0053] Figure 6 The stress test results of the scaffold G10B5 and the composite hydrogel G10B5 / PG-P@C10 enhanced by the electroactive scaffold; A corresponds to the stress loading-release stress-strain curve, B corresponds to the compression modulus, and C corresponds to the toughness;

[0054] Figure 7 Results of the intracellular ROS level detection under different component hydrogel conditions;

[0055] Figure 8 The results of the test of different component hydrogels on the expression levels of related proteins in cells; A corresponds to protein p21, B corresponds to the pro-inflammatory factor TNF-α, and C corresponds to type I collagen;

[0056] Fig. 9The results of the cell adhesion test on the composite hydrogel surface enhanced by the electroactive scaffold prepared in Example 4; wherein A corresponds to the fluorescent staining image of the cytoskeleton (red) and nucleus (blue) of chondrocytes, and B corresponds to the SEM image. DETAILED DESCRIPTION

[0057] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0058] Example 1 Preparation of a sandwich structure dual electroactive scaffold

[0059] The steps for preparing the sandwich structure dual electroactive stent provided in this embodiment are as follows:

[0060] (11) A 3D printing ink containing polycaprolactone (PCL) and graphene was prepared, and a conductive porous scaffold was obtained by 3D printing.

[0061] 10g of polycaprolactone (PCL) was dissolved in 70 mL of dichloromethane, and then 1g of graphene (G) was ultrasonically dispersed in the resulting solution to obtain a polycaprolactone / graphene (PCL / G) composite printing ink; after 10 hours of magnetic stirring and vacuum removal of bubbles, the printing ink was transferred to a 3D printing material tube and sealed with a stopper. A printing needle with a diameter of 0.26 mm was selected, and the 3D printer parameters were set as follows: extrusion pressure 0.5 MPa, printing speed 5 mm / min, layer thickness 0.18 mm, and printing wire gap 0.8 mm.

[0062] Based on the above 3D printing ink and according to the above 3D printing parameters, a conductive porous scaffold was printed and named G10.

[0063] (12) A polyvinylidene fluoride electrospinning solution in which barium titanate is uniformly dispersed is prepared, and a piezoelectric fiber film is formed on the upper and lower sides of the conductive porous support by electrospinning.

[0064] 0.075g BaTiO3 was ultrasonically dispersed in 9mL N,N-dimethylformamide (DMF), and then 1.5g polyvinylidene fluoride (PVDF) powder was added. The mixture was magnetically stirred at 60°C for 6h to form a uniform white solution. After cooling, 6 mL acetone was added and stirred for 3 hours to obtain an electrospinning solution. After overnight, the electrospinning solution was transferred to a syringe and spun on the upper and lower sides of the conductive porous scaffold obtained in step (11) using an electrospinning device at a flow rate of 0.1 mm / min and a voltage of 15 kV. The distance between the collector and the needle was kept at 15 cm. After the spinning, a piezoelectric composite fiber membrane (named B5) was obtained, and the sandwich structure dual electroactive scaffold was named G10B5. The sandwich structure dual electroactive scaffold was vacuum dried at 37°C overnight to fully evaporate and remove the residual solvent.

[0065] 1. Structural analysis

[0066] The conductive porous scaffold G10 prepared in step (11) was subjected to SEM test, and the results are shown in Figure 1 As shown in (a) and (b), the 3D printed scaffold has a vertically penetrating pore structure, and the surface of the G10 rubber wire is relatively rough; the SEM image of the cross section of the scaffold shows that the interlayer gap of the 3D printed scaffold has not collapsed significantly, which is basically consistent with the set model.

[0067] The sandwich structure dual electroactive scaffold G10B5 prepared in step (12) was subjected to SEM testing, and the results are shown in Figure 1 As shown in (c), the sandwich scaffold presents a sandwich structure with a layer of 3D printed scaffold sandwiched between two layers of fiber membranes, and the thickness of the fiber membranes on both sides is about 90 μm.

[0068] The sandwich structure dual electroactive scaffold G10B5 prepared in step (12) was subjected to EDS test, and the results are shown in Figure 2 As shown in the figure, during the electrospinning process, the fibers will be preferentially deposited on the support rubber wire, resulting in more fibers on the support rubber wire than on the surface of the holes after spinning. This is because the G10 support formed by the cross-arrangement of the conductive rubber wire will cause orderly fluctuations in the potential near the receiving point, thereby causing a certain pattern arrangement of the electrospun fiber film.

[0069] (II) Electrical performance analysis

[0070] To detect the electrical output of the sandwich-structure dual-electroactive scaffold under mechanical force stimulation, aluminum foil was attached to both sides of the sandwich-structure dual-electroactive scaffold as electrodes and then fixed with insulating tape; then an electrochemical workstation (660e, Chenhua, China) was used to record the output short-circuit current under the cyclic force of the linear motor (200 rpm). The test results are shown in Figure 2. Figure 3 shown.

[0071] The electrical output performance of the sandwich structure bracket is evaluated by the short-circuit current output under reciprocating stress. When the sample is compressed, the stress causes the lattice deformation of the piezoelectric phase, and a piezoelectric potential is generated inside the fiber membrane on the upper and lower surfaces of the sandwich structure. The free electrons in the electrode will flow through the external circuit, neutralizing the piezoelectric potential and generating current; when the external force is removed, the piezoelectric potential disappears, and the free electrons flow back to generate a reverse current. Figure 3 It can be seen that the sandwich structure dual electroactive stent provided in this embodiment has a large output current, indicating that both methods of improving the conductivity of the inner layer stent and enhancing the piezoelectricity of the fiber membrane can improve the electrical output performance of the sandwich structure under stress, and there is a synergistic relationship between the two.

[0072] 3. Effect of sandwich-structured dual electroactive scaffolds on cell migration ability

[0073] Under normal circumstances, stem cells exist in the stem cell niche. Degenerative discs release chemokines to promote stem cell migration and recruit them, but it is difficult for stem cells to break through the gap between the cartilage endplates and reach the inside of the disc. Therefore, enhancing the migration ability of stem cells is very important for repairing defective discs. Next, the Transwell migration experiment was used to evaluate the effect of electroactive materials on the migration ability of stem cells.

[0074] The specific operation steps are as follows: Place the sterilized G10B5 scaffold into a 24-well plate and add 600 μL of DMEM medium; Add 100 μL of BMSCs (bone marrow mesenchymal stem cell) suspension (10 5 The Transwell chamber (8 μm pore size) was placed in the corresponding 24-well plate with a scaffold and cultured in an incubator for 72 hours. During this process, some of the scaffold holes were stimulated with intermittent ultrasound (1 MHz, 0.8w, 10s) every 8 hours. Figure 4 As shown in A. After the culture was completed, the chamber was removed, the liquid in the chamber was aspirated, the cells inside were wiped off, and it was fixed in 4% paraformaldehyde. After fixation, it was washed with PBS and stained with crystal violet stain (Biyuntian, China). After the end, it was washed with PBS and observed under an optical microscope. Subsequently, the Transwell was placed in 1 mL of 33% glacial acetic acid solution to wash off the crystal violet, and the solution was aspirated into a 96-well plate. The absorbance value at 590 nm was read with an enzyme reader. The absorbance of the experimental group was compared with that of the blank control group to obtain the relative number of cells that migrated to the lower surface of the scaffold. The results are shown in Figure 4 As shown in B.

[0075] Without ultrasound, only a few cells in the G0 group were able to migrate through the inter-chamber gap to the bottom of the lower chamber; in contrast, more cells appeared on the lower surface of the chamber in the G10 and G10B5 groups. Compared with the corresponding non-ultrasounded groups (i.e., G0-US- and G10-US- groups), the number of cells on the lower surface of the chamber in the G0-US+ and G10-US+ groups after ultrasound application did not increase significantly; however, compared with the G10B5-US- group, the number of cells that passed through the lower wall of the chamber in the G10B5-US+ group increased significantly. Combined with the results of the relative number of migrating cells (e.g., Figure 4 C) analysis showed that since the electroactive scaffolds G10 and G10B5 are more similar to the electrophysiological microenvironment of the extracellular matrix, they can promote cell migration even without external ultrasonic stimulation; at the same time, the piezoelectric fiber layer also gives the G10B5 scaffold piezoelectric properties, which can convert mechanical energy into electrical stimulation under external ultrasonic stimulation, activate cells, and further enhance cell migration ability.

[0076] Example 2 Preparation of Antioxidant Nanozymes

[0077] The steps for preparing the antioxidant nanozyme provided in this embodiment are as follows:

[0078] (21) Preparation of Co-doped NiO nanoparticles.

[0079] 1.436 g Co(NO3)2·6H2O and 3.244 g 2-methylimidazole were dissolved in 100 mL methanol respectively to obtain two different solutions; the 2-methylimidazole solution was poured into the Co(NO3)2 solution and stirred vigorously for 12 min to obtain a uniform mixed solution; the solution was allowed to stand at room temperature for 24 h, the precipitate at the bottom was collected, then washed with deionized water and dried at room temperature for 24 h to obtain ZIF-67 powder.

[0080] 150 mg ZIF-67 and 150 mg NiCl2·6H2O were added to 50 mL ethanol, ultrasonically treated for 30 minutes, and then heated to 90°C for 1 hour after stirring at room temperature. The precipitate was then collected by centrifugation, washed with deionized water and dried at room temperature for 24 hours to obtain Co-Ni layered double hydroxide (Co-Ni LDH). The Co-Ni LDH powder was then heated to 300°C at a rate of 2.5°C / min and calcined for 3 hours to obtain Co-doped NiO (CNO) nanoparticles.

[0081] (22) Co-doped NiO nanoparticles are uniformly dispersed in deionized water, the resulting dispersion is mixed with a dopamine solution (dopamine is added to deionized water and mixed uniformly), the pH is adjusted, and the solution is stirred in the dark. The resulting product is centrifuged, washed, and freeze-dried to obtain an antioxidant nanozyme.

[0082] The obtained 20 mg Co-doped NiO (CNO) nanoparticle powder was ultrasonically dispersed in 30 mL deionized water and then mixed with 20 mL dopamine solution (2.5 mg / mL); the pH value of the mixed solution was adjusted to 8.5 with Tris-hydrochloric acid buffer and stirred for 24 h in the dark; the precipitate was then collected by centrifugation, washed with deionized water and freeze-dried to obtain PDA@CNO powder, i.e., antioxidant nanozyme.

[0083] The morphology test results of the antioxidant nanozyme prepared in this example are as follows Figure 5 As shown. Figure 5 It can be seen that after DA was polymerized on the CNO surface, PDA@CNO nanoparticles with obvious core-shell structure were obtained.

[0084] Example 3 Preparation of composite hydrogel precursor solution

[0085] The steps for preparing the composite hydrogel precursor solution provided in this embodiment are as follows:

[0086] (31) Polyvinyl alcohol was added to the glycerol aqueous solution and dissolved by heating and stirring to obtain a PVA hydrogel precursor solution.

[0087] Glycerol was mixed with deionized water to form a glycerol aqueous solution (Vglycerol:Vwater=2:8). According to the final concentration of polyvinyl alcohol (PVA) of 15% (w / v), polyvinyl alcohol (PVA) particles were weighed and added to the above glycerol aqueous solution, and stirred at 95°C for 4h to completely dissolve, to obtain a 15% (w / v) PVA hydrogel precursor solution.

[0088] (32) Antioxidant nanozymes were added to the PVA hydrogel precursor solution and dispersed evenly, and then gelatin was added and stirred until the gelatin was dissolved to obtain a composite hydrogel precursor solution.

[0089] The PVA hydrogel precursor solution was cooled to 60°C, and PDA@CNO nanozyme (prepared in Example 2, with a final concentration of 1‰ (w / v)) was added. After uniform ultrasonic dispersion, gelatin (Gel) powder (final concentration of 5% (w / v)) was added and stirred at a constant temperature of 60°C for 3 h. After the gelatin was completely dissolved, a composite hydrogel precursor solution was obtained.

[0090] Example 4 Preparation of intervertebral disc repair material

[0091] The sandwich structure dual electroactive scaffold prepared in Example 1 was immersed in the defoamed composite hydrogel precursor solution, subjected to repeated vacuum pumping-degassing operations, repeated freezing-thawing operations, and finally annealing treatment to obtain the electroactive scaffold-enhanced composite hydrogel, i.e., the intervertebral disc repair material.

[0092] Specifically, the composite hydrogel precursor solution prepared in Example 3 is defoamed and poured into the mold, and then the G10B5 stent prepared in Example 1 is placed in the mold so that the solution covers the upper surface of the stent. The mold is quickly transferred to a vacuum drying oven, the temperature of the vacuum drying oven is set to 37°C, and the vacuum is evacuated until the vacuum degree drops below 100Pa, and the air is released after maintaining for 30 seconds; the evacuation-release operation is repeated 3 times to allow the hydrogel precursor solution to fully penetrate the entire stent through the interlayer pores. After cooling to room temperature, freeze-thaw 3 times at -20°C and room temperature, and then annealed in a 50°C oven for 5 hours, and finally a composite hydrogel enhanced by an electroactive stent is obtained, named G10B5 / PG-P@C10.

[0093] 1. Mechanical properties analysis

[0094] The scaffold G10B5 and the electroactive scaffold-enhanced composite hydrogel G10B5 / PG-P@C10 were subjected to uniaxial compression tests using a universal mechanical testing machine (Instron 5967, Instron, USA) to obtain stress-strain curves, and the compression modulus of the scaffold G10B5 and the electroactive scaffold-enhanced composite hydrogel G10B5 / PG-P@C10 was calculated based on the stress-strain curves. The sample size used in this experiment is length × width × height = 10 × 10 × 10 mm 3 , the compression strain rate is 1 mm / min, and the compression ratio is 40%. Three samples are tested in each group.

[0095] from Figure 6 It can be seen that the compressive strength of G10B5 / PG-P@C10 is significantly higher than that of G10B5. Figure 6 B) shows that the compression modulus of G10B5 / PG-P@C10 (10.14 MPa) is significantly higher than that of the G10B5 scaffold (7.37 MPa). This is because in the G10B5 / PG-P@C10 system, the interlayer gaps of the G10B5 scaffold are filled with hydrogels. When compressed, the interlayer PG-P@C10 hydrogel will resist the stress and provide a certain support. It is worth noting that after being reinforced by the scaffold, the compression modulus of G10B5 / PG-P@C10 can match the strength of the natural intervertebral disc, and has the potential to replace it to maintain the height of the intervertebral disc. In addition, compared with G10B5, the stress-strain hysteresis loop area of ​​G10B5 / PG-P@C10 is larger ( Figure 6 A), indicating that during stress loading and unloading, G10B5 / PG-P@C10 can dissipate more energy and has stronger toughness. It is calculated that the toughness of G10B5 / PG-P@C10 is about twice that of G10B5 ( Figure 6C). This is due to the energy dissipation mechanism in the PG-P@C10 hydrogel system, namely the reversible hydrogen bond interaction between polymer chains. When stress is applied, the hydrogen bonds are broken, and when the stress is removed, the hydrogen bonds are reformed, making the composite system more resilient than a simple scaffold.

[0096] 2. Analysis of in vitro biological properties of hydrogels

[0097] To further study the protective effect of PG-P@C hydrogel containing functional nanozymes on cells in an environment with high ROS levels, a culture medium containing H2O2 was used to simulate a high oxidation level environment to stimulate the cells to enter an oxidative stress state. The cells were then co-cultured with hydrogel extracts of different components, and the levels of related molecules in the cells were characterized.

[0098] The hydrogels of different components were freeze-dried and then sterilized by plasma for later use. The sterilized hydrogels were weighed and soaked in DMEM culture medium (50 mg / mL), and the hydrogel extracts of different components were obtained after two days.

[0099] Chondrocytes were added to 24-well plates (10 5 / well), and cultured in a 37℃ incubator for 1 day. After aspirating the culture medium, add DMEM (high glucose) complete culture medium containing 5 μM H2O2, and culture in a 37℃ incubator for 1 hour to make the cells enter an oxidative stress state. Then aspirate the culture medium containing H2O2, wash the well plate with PBS, add the corresponding hydrogel extract (1 mL / well), and culture in a 37℃ incubator for 24 hours to study the effect of different hydrogels on cell behavior under oxidative stress.

[0100] 1. Detection of intracellular ROS levels

[0101] The intracellular ROS levels were measured after co-culture with extracts of different hydrogel components (P, PG, PG-P@C10). The control group (Control) was a culture medium without hydrogels during pretreatment, and a culture medium without H2O2 was used during subsequent culture; the experimental groups were named according to the different components of hydrogels during pretreatment.

[0102] Preparation of hydrogel P: The 15% (w / v) PVA hydrogel precursor solution prepared in Example 3 was defoamed and cooled to room temperature, and then freeze-thawed three times at -20°C and room temperature, and then annealed in an oven at 50°C for 5 hours to obtain a glycerol-reinforced PVA hydrogel, named P.

[0103] Preparation of hydrogel PG: The 15% (w / v) PVA hydrogel precursor solution prepared in Example 3 was cooled to 60°C, 5% (w / v) Gel powder was added, and the mixture was stirred at a constant temperature for 3 hours. After the gelatin was completely dissolved, the mixture was defoamed and cooled to room temperature, and then frozen and thawed three times at -20°C and room temperature, and then annealed in an oven at 50°C for 5 hours to finally obtain a PVA-Gel hydrogel named PG.

[0104] Preparation of hydrogel PG-P@C10. The composite hydrogel precursor solution prepared in Example 3 was defoamed and cooled to room temperature, then frozen and thawed three times at -20°C and room temperature, and then annealed in an oven at 50°C for 5 hours to finally obtain a PVA-Gel hydrogel containing antioxidant nanozymes, named PG-P@C10.

[0105] Normal NP cells were cultured at 10 5 The cells were seeded in a 96-well plate at a density of 100 μg / well. Subsequently, the cells were pretreated with culture medium containing P (50 mg / mL), PG (50 mg / mL), and PG-P@C10 (50 mg / mL) for 0.5 h, and the culture medium was discarded. In order to study the protective effect of hydrogels with different components on NP cells in a strong oxidative microenvironment, a culture medium containing H2O2 (100 μM) was then used to simulate a high-level ROS microenvironment, and the cells were cultured for 24 h before being serially characterized.

[0106] First, the DCFH-DA fluorescent probe was used to detect the intracellular ROS level. Figure 7 The green fluorescence intensity in the control group was very high, indicating that the cells entered a state of oxidative stress under the stimulation of H2O2; strong green fluorescence signals also appeared in the P and PG groups, while the green fluorescence intensity in the PG-P@C10 group decreased, indicating that the antioxidant nanozyme gave the hydrogel certain antioxidant properties and could restore the redox balance in the oxidative stress cells.

[0107] 2. Cell Immunofluorescence Staining

[0108] Oxidative stress can cause a series of abnormal reactions including cell senescence, inflammatory response and imbalance of extracellular matrix metabolism, which hinder the tissue repair process. Therefore, immunofluorescence staining was used to test the expression levels of related proteins (p21, proinflammatory factor TNF-α and type I collagen) in each group of cells.

[0109] The cultured chondrocytes were first fixed with 4% paraformaldehyde, then permeabilized with 0.1% Triton-X, and blocked with 5% BSA (Bio, China). Then, 200 μL of primary antibody 5% BSA dilution was used for treatment: anti-p21Waf1 / Cip 1 (1:400, Cell Signaling Technology, China), anti-TNF-α (1:200, Proteintech, USA), Anti-COL1A1 (1:200, Solarbio, China). After incubation in a refrigerator at 4°C overnight, the cells were incubated with a secondary antibody linked to AlexaFluor594 (Abcam, UK) for 1 hour, and the cytoskeleton and nucleus were stained with FITC-phalloidin (AAT, USA) and DAPI (Solarbio, China), respectively. The cells were observed under a fluorescence microscope. The results are shown in Figure 2. Figure 8 shown.

[0110] Figure 8 A is an immunofluorescence staining (red) image of the cell senescence-related protein p21 (blue fluorescence represents the cell nucleus). A small number of cells in the control group, P and PG hydrogel groups showed red fluorescence, indicating that chondrocytes aged under the stimulation of H2O2, while P and PG hydrogels could not change the cellular senescence state; in contrast, after the introduction of antioxidant nanozymes into the hydrogels, the red fluorescence intensity in the PG-P@C10 group was significantly reduced, indicating that the introduction of antioxidant nanozymes into the hydrogels can reverse cell senescence caused by high ROS levels in the environment.

[0111] TNF-α is one of the most important pro-inflammatory factors in the human body, which has the function of recruiting immune cells and promoting the secretion of other inflammatory factors. The level of TNF-α in cells is measured to reflect the inhibitory effect of hydrogels with different components on cell inflammatory response. Figure 8 B is the immunofluorescence staining (red) result of TNF-α after co-culture of chondrocytes stimulated by H2O2 and hydrogel extracts of different components (nucleus: blue). A large amount of red fluorescence appeared in the control group, indicating that a large amount of TNF-α was produced in chondrocytes under the stimulation of H2O2, triggering a strong inflammatory response; in comparison, the red fluorescence of the PG-P@C10 hydrogel group was significantly reduced, indicating that PG-P@C10 hydrogel can inhibit cell inflammatory response.

[0112] Subsequently, in order to evaluate the effects of hydrogels with different components on extracellular matrix metabolism under oxidative stress, the content of type I collagen in chondrocytes was detected. The results of immunofluorescence staining of type I collagen (red) are shown in Figure 2. Figure 8 C shows that compared with the control group, the red fluorescence intensity of the P and PG hydrogel groups did not change significantly; while the red fluorescence intensity of the PG-P@C10 group increased.

[0113] Therefore, PG-P@C10 hydrogel can reduce cell senescence, reduce cellular inflammatory response, and enhance extracellular matrix synthesis by reducing intracellular ROS levels under oxidative stress. These functions are crucial for improving cell metabolic abnormalities caused by the pathological microenvironment of the intervertebral disc and promoting the integration of materials with surrounding tissues.

[0114] 3. Cell adhesion on scaffold-reinforced composite hydrogel

[0115] Cell adhesion is a very important step in the integration of materials and surrounding tissues, which will affect the subsequent life activities of cells and the repair and reconstruction of damaged tissues.

[0116] The G10B5 / PG-P@C10 composite hydrogel was freeze-dried and sterilized with plasma for later use. The sterilized material was placed in a 48-well plate, and 500 μL (10 5 / mL), and cultured in a 37°C incubator. During the culture process, ultrasonic stimulation was intermittently applied to some wells (1 MHz, 0.8w, once every 8 hours, each time lasting 10 seconds). After 48 hours of culture, the culture medium was discarded and rinsed with PBS; the samples were first fixed with 4% paraformaldehyde, and then the cells were permeabilized with 0.1% Triton-X, and the cells were blocked with 5% BSA (Bio, China). The cytoskeleton and cell nucleus were stained with phalloidin (Actin-Tracker Red-555, Biyuntian, China) and DAPI, respectively, and the cell number and morphology were observed under a laser confocal microscope (N-SIM / A1R MP+, Nikon, Japan). The results are shown in Fig. 9 As shown in A. After that, the sample was gradient dehydrated, freeze-dried, and sprayed with gold, and the cell morphology was observed by SEM, as shown in Fig. 9 As shown in B.

[0117] like Fig. 9 As shown in A, without ultrasonic stimulation, chondrocytes can adhere to the surface of G10B5 / PG-P@C10 composite hydrogel, and some cells can be observed to spread; in contrast, with intermittent ultrasonic stimulation during the culture process, the amount of blue fluorescence increased, and the cytoskeleton signal intensity was stronger and more uniform. To further observe the morphology of chondrocytes adhered to the surface of G10B5 / PG-P@C10, the samples were freeze-dried and observed under a scanning electron microscope. The results are shown in Fig. 9 B. The cells adhered to the surface of G10B5 / PG-P@C10 showed a good spreading state and extended pseudopodia; in the group with intermittent ultrasound treatment, the pseudopodia of the cells were more numerous and more extended. The above results show that the G10B5 / PG-P@C composite hydrogel itself has good cell adhesion ability, and can further promote cell adhesion by capturing energy in the environment and converting it into electrical stimulation, thus facilitating the integration of materials and tissues.

[0118] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. An intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration, characterized in that: include: A sandwich-structured dual-electroactive scaffold, and a composite hydrogel attached to the dual-electroactive scaffold; The sandwich-structured dual-electroactive scaffold includes a conductive porous scaffold with a conductive through-channel structure and piezoelectric fiber films located on the upper and lower sides of the conductive porous scaffold; the conductive porous scaffold is obtained by 3D printing with a 3D printing ink containing graphene; the composite hydrogel includes a hydrogel and an antioxidant nanozyme uniformly dispersed in the hydrogel; the antioxidant nanozyme is a core-shell structured nanoparticle with a Co-Ni bimetallic oxide as a core and polydopamine as a shell.

2. The intervertebral disc repair material based on the staged treatment strategy for intervertebral disc degeneration according to claim 1, characterized in that: The 3D printing ink also includes a fat-soluble biodegradable material; the fat-soluble biodegradable material is at least one of polycaprolactone, polyhydroxyalkanoate, and polylactic acid; and the mass ratio of the fat-soluble biodegradable material to graphene is 9 to 10:

1.

3. The intervertebral disc repair material based on the staged treatment strategy for intervertebral disc degeneration according to claim 1, characterized in that: The piezoelectric fiber film is a polyvinylidene fluoride fiber film doped with barium titanate; the piezoelectric fiber film is obtained by electrostatic spinning; the mass ratio of polyvinylidene fluoride to barium titanate is 18-20:

1.

4. The intervertebral disc repair material based on the staged treatment strategy for intervertebral disc degeneration according to claim 1, characterized in that: The hydrogel is obtained by solidifying a hydrogel precursor solution containing polyvinyl alcohol and gelatin.

5. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of sandwich structure dual electroactive scaffolds, The following steps are included: (11) preparing a 3D printing ink comprising a fat-soluble biodegradable material and graphene, and obtaining a conductive porous scaffold by 3D printing; (12) preparing a polyvinylidene fluoride electrospinning solution in which barium titanate is uniformly dispersed, and forming a piezoelectric fiber film on the upper and lower sides of the conductive porous support by electrospinning; (2) Preparing antioxidant nanozymes, comprising the following steps: (21) Preparation of Co-doped NiO nanoparticles; (22) Co-doped NiO nanoparticles are uniformly dispersed in water, the resulting dispersion is mixed with a dopamine solution, the pH is adjusted to 8-9, and the mixture is stirred in the dark; the resulting product is centrifuged, washed, and freeze-dried to obtain an antioxidant nanozyme; (3) Preparing a composite hydrogel precursor solution, comprising the following steps: (31) adding polyvinyl alcohol to the glycerol aqueous solution, heating and stirring to dissolve, and obtaining a PVA hydrogel precursor solution; (32) adding the antioxidant nanozyme to the PVA hydrogel precursor solution and dispersing it evenly, then adding gelatin and stirring until the gelatin is dissolved to obtain a composite hydrogel precursor solution; (4) Preparation of intervertebral disc repair materials The sandwich structure dual electroactive scaffold prepared in step (1) is immersed in the defoamed composite hydrogel precursor solution, subjected to repeated vacuum pumping-degassing operations for more than three times, and then subjected to repeated freezing-thawing operations for more than three times, and finally subjected to annealing treatment to obtain the electroactive scaffold-enhanced composite hydrogel, i.e., the intervertebral disc repair material.

6. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to claim 5, characterized in that: In step (11), the fat-soluble biodegradable material is first dissolved in a first organic solvent, and then graphene is uniformly dispersed in the resulting solution to obtain a 3D printing ink; the first organic solvent is dichloromethane or tetrahydrofuran.

7. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to claim 5, characterized in that: In step (12), barium titanate is first evenly dispersed in a second organic solvent, polyvinylidene fluoride is then added, and then stirred at 60-70°C for 6-8 hours to form a uniform white solution; cooled to room temperature, and then a third organic solvent is added, and stirred evenly to form an electrospinning solution; then a piezoelectric fiber film is formed on the upper and lower sides of the conductive porous support by an electrospinning method, and then the residual solvent is removed by vacuum drying to obtain a sandwich structure dual electroactive support; the second organic solvent is N,N-dimethylformamide or N-methylpyrrolidone; the third organic solvent is one of acetone, ethyl acetate, butanone, and cyclohexanone.

8. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to claim 5, characterized in that: In step (21), cobalt salt and 2-methylimidazole are dissolved in a fourth organic solvent at a molar ratio of 1:7-9 to obtain corresponding solutions, and the two solutions are mixed and stirred to react to obtain a uniform mixed solution; the mixed solution is allowed to stand, the precipitate is collected, and then washed and dried to obtain ZIF-67 powder; then the ZIF-67 powder and the nickel salt are mixed in a fifth organic solvent at a mass ratio of 1:1, stirred evenly, heated to 90-95°C for reaction for 1-2h, and then centrifuged, washed, and dried to obtain Co-Ni layered double hydroxide; the Co-Ni layered double hydroxide is calcined at 290-310°C for 3-3.5h to obtain Co-doped NiO nanoparticles; the cobalt salt is cobalt nitrate or cobalt chloride; the nickel salt is nickel chloride or nickel sulfate; the fourth organic solvent is methanol or dimethyl sulfoxide; the fifth organic solvent is one of ethanol, isopropanol, and dimethoxymethane.

9. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to claim 5, characterized in that: In step (3), the final concentration of polyvinyl alcohol in the composite hydrogel precursor solution is 12%~18% w / v, the final concentration of antioxidant nanozyme is 0.5‰~1‰ w / v, and the final concentration of gelatin is 4%~6% w / v.

10. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to claim 5 or 9, characterized in that: In step (31), the glycerol aqueous solution is obtained by mixing glycerol and water in a volume ratio of 2:

8.

11. The method for preparing an intervertebral disc repair material based on a staged treatment strategy for intervertebral disc degeneration according to claim 5, characterized in that: The vacuum pumping-degassing operation is: first evacuate until the vacuum degree drops below 100Pa, maintain for 30-35s, and then release to standard atmospheric pressure; the freezing-thawing operation is: cycle freezing-thawing between -20°C and room temperature; the annealing condition is annealing at 40-50°C for 4-6h.

12. Use of the intervertebral disc repair material according to any one of claims 1 to 4 in preparing an intervertebral disc repair device.

Citation Information

Patent Citations

  • Biphase piezoelectric composite scaffold for osteochondral in-situ regeneration and preparation method of biphase piezoelectric composite scaffold

    CN117138107A

  • Biological piezoelectric crystal hydrogel as well as preparation method and application thereof

    CN118681069A